Hydro-Geomorphology (IntechOpen, 2023)
Knowledge has no limits and everyone has the opportunity to gain it and expand the view and horizon of understanding. Nothing in this world remains permanent, everything changes. Hence the field of morphology of the Earth (geomorphology) provides a basis for exploring, understanding and comprehending the forms and processes that occur in our surrounding. This book presents some of the ideas and understanding about geomorphology: Learn about the effect of deforestation and then reforestation on river channel morphology. Understand the composite mathematical modelling for continuous simulations of hydro-geomorphological processes. Know about the process-response models for estimation of cliff erosion and its quantitative predictions. Grow your knowledge about various geomorphometric tools that are available in freely available GIS software.